2017
DOI: 10.4103/jehp.jehp_78_16
|View full text |Cite
|
Sign up to set email alerts
|

The effect of supportive educative program on the quality of life in family caregivers of hemodialysis patients

Abstract: BACKGROUND:Previous studies showed that family caregivers of hemodialysis patients have low level of quality of life. However, these caregivers are mostly neglected, and no studies are available on improving their quality of lives. Therefore, this study aimed to examine the effects of supportive educative program on the quality of life in family caregivers of hemodialysis patients.MATERIALS AND METHODS:A randomized controlled clinical trial was conducted on 76 family caregivers of hemodialysis patients referre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 28 publications
1
21
0
3
Order By: Relevance
“…Support programs have been reported to help caregivers develop coping strategies that could reduce the burden of caregiving 4244. The caregivers of CKD patients must be seen by Clinicians as important stakeholders in the successful management of CKD patients, hence their psychological needs must be met by adopting this supportive approach.…”
Section: Discussionmentioning
confidence: 99%
“…Support programs have been reported to help caregivers develop coping strategies that could reduce the burden of caregiving 4244. The caregivers of CKD patients must be seen by Clinicians as important stakeholders in the successful management of CKD patients, hence their psychological needs must be met by adopting this supportive approach.…”
Section: Discussionmentioning
confidence: 99%
“…26 No. 5 -2020 erate (10)(11)(12)(13)(14), moderate to severe (15)(16)(17)(18)(19) and severe (20). The Cronbach alpha for PHQ-9 is 0.88 (17); it was 0.80 for this study.…”
Section: Caregiver's Depressive Symptomsmentioning
confidence: 59%
“…The family caregiver burden in primary care clinics is linked to psychological, socioeconomic, and physical consequences (11,12). However, the quality of life of family caregivers of patients on haemodialysis tends to be neglected, although they are distressed emotionally, financially and psychologically (13). The burden on caregivers of dialysis patients has been acknowledged in recent investigations in the Middle East (4,10).…”
Section: Introductionmentioning
confidence: 99%
“…In this review, 1-8 groups of caregivers took part in these sessions, the sessions spanned from 2 to Full-size  DOI: 10.7717/peerj.11713/fig- 1 6 weeks and the number of hours of intervention delivered to caregivers ranged from 4 to 16 h. Coordinators of group sessions had different professional backgrounds. Three studies reported a nephrologist, a psychiatric nurse, and/or an HD nurse as the person responsible for delivering the content of the sessions (Ghane et al, 2016;Ghane et al, 2017;Rabiei et al, 2020). The remaining studies were conducted by the authors of the articles.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The majority of them (n = 4) also used booklets or pamphlets (Ghane et al, 2016;Rabiei et al, 2020;Sotoudeh, Pahlavanzadeh & Alavi, 2019;Ashghali Farahani et al, 2016). Three studies mentioned having validated these materials prior to use (Ghane et al, 2016;Ghane et al, 2017;Sotoudeh, Pahlavanzadeh & Alavi, 2019). Furthermore, after implementing the intervention with the intervention group, one study organized two supervised meetings with the control group, where participants could discuss their issues, feelings, and experiences (Sotoudeh, Pahlavanzadeh & Alavi, 2019).…”
Section: Control Groupsmentioning
confidence: 99%